Phenytoin induced dystonia - Tarık Acar; Gülsüm Alkan; Hüseyin Çaksen; Birsen Ertekin; Mehmet Ergin; Sedat Koçak; Başar Cander (The Turkish Journal of Pediatrics)
The abnormalities of dopaminergic activity in the basal ganglia have been emphasized to be effective in dystonia. We hereby report a case of a 2.5-year-old male patient who presented with tonic-clonic sezures and who developed dystonia after being given phenytoin. Biperidene hydrochloride was administered intramuscularly; primidone was added to the treatment regimen. After a 7-day-follow-up at the hospital, the patient had no dystonia and was discharged.